A micro-electromechanical systems based vibration energy harvester with aluminum nitride piezoelectric thin film deposited by pulsed direct-current magnetron sputtering. (15th October 2018) - He, Xianming; Wen, Quan; Lu, Zhuang; Shang, Zhengguo; Wen, Zhiyu
Graphical abstract: A MEMS-based vibration energy harvester with highly c-axis oriented AlN piezoelectric thin film is designed and investigated, which has maximum output power density of 854.55 μW/cm 3 /g 2 . Furthermore, the high-precision coupled distributed parameter model of the device is derived and verified. Highlights: A MEMS-based AlN energy harvester with high output power density is designed. The highly c-axis oriented aluminum nitride piezoelectric thin film is deposited. The high-precision coupled distributed parameter model is derived and verified. The engine fault monitoring node based on the AlN energy harvester is designed. Abstract: Piezoelectric vibration-based energy harvesting is a promising alternative for the durable and reliable power supplies for the low-powered wireless sensor networks nodes. However, improving the piezoelectric vibration-based energy harvester's energy conversion efficiency related closely on the structure parameters and materials become significant and urgent. In this paper, a micro-electromechanical systems (MEMS) cantilever-based aluminum nitride (AlN) vibration energy harvester is presented, modeled, optimized and fabricated. The c-axis oriented AlN piezo thin film is deposited by the pulsed direct-current magnetron sputtering with the optimized process parameters. Furthermore, the coupled distributed parameter model is derived in detailed, verified by using the ANSYS finite element analysis, and applied to the optimization of structural parameters and load resistance. Finally, the prototype of the device is fabricated by the standard bulk-silicon technology. As a result, at 1 g and 210.85 Hz, the maximum output root mean square (RMS) voltage can reach to 4.66 V, the output average power and output average power density of the prototype is up to 56.4 μW and 854.55 μW/(cm 3 ·g 2 ) at a load resistance of 146.6 kΩ, respectively. The experimental results agree well with theoretical analysis. The derived CDP model has an important and effective guiding role in cantilever based piezoelectric vibration energy harvester for structural design and performance optimization, especially for the device with long tip mass. The prototype has wide application prospects in the fields of the wireless sensor network node such as the structural health monitoring system.